1999
DOI: 10.1021/ma9906332
|View full text |Cite
|
Sign up to set email alerts
|

Structure Development during the Melt Spinning of Polyethylene and Poly(vinylidene fluoride) Fibers by in Situ Synchrotron Small- and Wide-Angle X-ray Scattering Techniques

Abstract: In the present study, the structural and morphological development during melt spinning of polyethylene and poly(vinylidene fluoride) fibers was studied using simultaneous in-situ synchrotron small-and wide-angle X-ray scattering (SWAXS) techniques. The spinning apparatus consisted of a single screw extruder, which was mounted on a horizontal platform that could be translated in the vertical direction allowing different spinneret distances to be sampled with the X-ray beam. Effects of take-up speed (10.6-61.0 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
86
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 103 publications
(99 citation statements)
references
References 39 publications
13
86
0
Order By: Relevance
“…Similar equatorial streak development was reported for polyethylene and poly (vinylidene fluoride) fibers by Schultz et al 14,15 . They suggested that the streak corresponds to the development of shish crystal, because it was vanished when the crystal reflection appeared 15 .…”
Section: Saxs Imagessupporting
confidence: 86%
See 1 more Smart Citation
“…Similar equatorial streak development was reported for polyethylene and poly (vinylidene fluoride) fibers by Schultz et al 14,15 . They suggested that the streak corresponds to the development of shish crystal, because it was vanished when the crystal reflection appeared 15 .…”
Section: Saxs Imagessupporting
confidence: 86%
“…measured both WAXD and small-angle x-ray scattering (SAXS) images simultaneously for the spinning process of polyamide 6, polyethylene, and poly (vinylyden fluoride) 14,15 . For the drawing process, most on-line measurement studies fall into one of two categories; batch drawing under small strain rate [20][21][22][23][24][25][26][27][28][29][30][31][32] , and draw ratio dependence of continuous drawing [33][34][35][36] .…”
Section: Introductionmentioning
confidence: 99%
“…Here, Q s , depends upon the volume fraction of crystallites but may also be affected by the volume of material at the X-ray point. In this case, the decrease in tape volume would decrease Q s , however it is only a scaling factor in the correlation function and other authors [34,38] assume that any reduction is small. Thus generally, an increase in Q s correlates to an increase in scattering from the crystallization in the polymer tape.…”
Section: X-ray Scattering Measurements and Data Analysismentioning
confidence: 89%
“…Other groups have also seen similar results when investigating the early stages of the fibre melt spinning process. Samon et al [34][35][36][37][38] have reported on the crystalline development in melt spinning of several polymers (nylon 6, PE, PVDF and poly(oxymethylene) (POM)) again using SAXS/WAXS as a function of distance and take-up speed from the spinneret. Equatorial SAXS scattering was seen to develop before the meridional SAXS patterns, which was interpreted as indicating the initial stages of shish-kebab or microfibril crystallization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation